КӨРКЕМ ӘДЕБИЯТТАҒЫ ИМПРОВИЗАЦИЯ ҚУБЫЛЫСЫ: ИЗЕРТЛЕНИЎИ ТАРИЙХЫ МЕНЕН ТЕОРИЯСЫНЫҢ АЙЫРЫМ МӘСЕЛЕЛЕРИ - Матимов, К.Г. (SCIENCE and SOCIETY, 2024)
Author depicts improvization skill especially its traditions as one of the special tradition of poetic creative method in performing poems, moreover as one of the technique of creating poems. Poet-improvizor in poem creating process uses techniques of improvization, poetic forms, literary methods, expressive means and author with the help of this means can widely describe poetic world.